Frattesina: la prospettiva europea - Pearce, Mark (Accademia dei Lincei, 2018)
In this paper I explore what makes Frattesina (Fratta Polesine RO) a key site in Europe during the transition from the Bronze Age to the Iron Age. Frattesina had an important role as an industrial and commercial centre, tied into a trade network that attests direct and indirect contacts from the Baltic as far as the East Mediterranean. I believe, however, that its real significance lies in its potential to illuminate the commercial relations of the Mediterranean ‘dark’ age, the period between the Mycenaean exchange in the West in the Middle and Recent Bronze Age and the presence of Greeks in the eighth century BC, first as traders but then, after the foundation of Pithekoussai and Cumae in the central Tyrrhenian, as colonisers. Frattesina also documents the transitional period between the Bronze Age and the Iron Age, when the archaeological cultures emerge that can be seen as the direct antecedents of the societies in the Italian peninsula with which the ancient sources tell us the Greeks and later the Romans came into contact. A range of artefacts in local or exotic raw material found at Frattesina illustrate its role as a commercial node, and in this paper I discuss the following classes of material in order to untangle their historical and cultural significance: amber, pottery, glass, ivory, ostrich egg shell and metal; there is also evidence for considerable antler-working.